2023
DOI: 10.1161/jaha.122.028766
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Physiology and Ventricular‐Vascular Interactions in Young Patients After Heart Transplantation

Abstract: Background In patients after heart transplantation, systemic arterial hypertension and enhanced central aortic stiffness contribute to increased ventricular afterload, which might lead to graft dysfunction. The aim of our study was to characterize systemic arterial elastance and its impact on left ventricular function and ventriculo‐arterial coupling in a cohort of children, adolescents, and young adults after heart transplantation using invasive conductance catheter technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These authors observed that patients submitted to heart transplantation present impaired ventricular-arterial coupling at rest and in response to inotropic stimulation, despite having preserved left ventricular contractile reserve. An abnormal response in vascular function leading to an increase in afterload appears to be a significant factor that may play a role in the development of late graft failure 35 .…”
Section: Discussionmentioning
confidence: 99%
“…These authors observed that patients submitted to heart transplantation present impaired ventricular-arterial coupling at rest and in response to inotropic stimulation, despite having preserved left ventricular contractile reserve. An abnormal response in vascular function leading to an increase in afterload appears to be a significant factor that may play a role in the development of late graft failure 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adults with rToF or ASD have diminished endothelial function ( Scicchitano et al, 2019 ; Goeder et al, 2022 ). Patients after heart-transplantation also have increased arterial elastance which has been proposed to play a role in late graft failure ( Latus et al, 2023 ) but the prognostic value has not to our knowledge been studied in patients with ASD or rToF. It is however shown that patients with non-complex CHD have an increased risk of cardiovascular disease, disproportionate to the burden of other known risk factors ( Saha et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%